Study on strength and constitutive model of frozen calcareous clay under multi-factor interaction - Feng, Jihao; Rong, Chuanxin; Shi, Hao; Wang, Bin; Wang, Zhi; Guo, Longhui; Tu, Zhuo; Long, Wei; Wu, Dong; Wang, Xueyan (Frontiers in Earth Science, 2024)
The investigation into the complex mechanical properties of frozen calcareous clay under multi-factor interaction holds significant importance for the reliability and durability of engineering in cold regions. This study investigates the strength properties of frozen calcareous clay under different interaction levels by designing a four-factor, four-level orthogonal test that incorporates temperature, confining pressure, dry density, and water content. The study aimed to assess the sensitivity of each factor to failure stress, and establish an intrinsic model based on the Duncan-Chang model considering temperature, confining pressure, and water content. The results indicated that the stress-strain curves exhibit strain-hardening characteristics across various interaction levels. These curves can be divided into elastic and elastic-plastic phases, with the slope of the elastic phase and the stress value at the inflection point increasing with decreasing temperature and increasing confining pressure. When the confining pressure is maintained constant, the failure stress is negatively correlated with temperature. When the temperature is maintained constant, the failure stress is positively correlated with confining pressure. Sensitivity analysis shows that the influence of each factor on failure stress is as follows: temperature > confining pressure > dry density > water content. Additionally, the influence of temperature and confining pressure on failure stress is markedly greater than that of water content and dry density. The evolution of unfrozen water content follows three stages: sharp reduction, rapid reduction, and slow reduction. Verification against experimental data confirmed that the modified constitutive model effectively reflects the stress-strain relationship of frozen calcareous clay under the interaction of multiple factors.